Co-branding of compass shoes on social networks - Basit, Abdul; Munfarida, Siti; Rully, Rully; Vidal, Mateo Jose A. (Faculty of Communications Science, Dr. Soetomo University, 2021)
Today's competition requires each product to develop a co-branding strategy in reaching the market, especially in the digital era where social networking is a space to build brand identities. So this research was conducted to find out how to co-brand Compass Shoes on social networks. To find out how much influence the co-branding variable has on social networks, seen from the dimensions of social networks by measuring social networks—using a quantitative-explanatory methodology, a data collection using a random questionnaire with a total of 398 respondents who meet the characteristics of the sample. The results of this study have a hypothesis where the exogenous variable, namely co-branding, has a significant effect on the endogenous variable, namely social networking. Creating co-branding, of course, must have a strong strategy in innovation and be able to understand consumer desires by providing collaboration space to build a shared identity.